Jesús Moncada o l'art de contar amb la mà esquerra - -, - (Caplletra. Revista Internacional de Filologia, 1997)
The author of the article analyses a short-stories collection by Jesús Moncada from the point of view of their title: Històries de la mà esquerra. Vicent Alonso considers that the title is a key element of the form of publication of contemporary short-stories. And, consequently, it is a key element of their interpretation. The author tries to define the characteristics of a way of story telling (telling things indirectly) which requires a different role from the reader of these kinds of texts.